Respiratory Function Tolerance of Rats with Vaying Degrees of Thoracic Volume Reduction. Issue 4 (1st March 2023) - Deng, Jiuxu; Chen, Xiao‐Kun; Guo, Fu‐Zheng; Huang, Wei; Zhu, Feng‐Xue; Wang, Tian‐Bing; Jiang, Bao‐Guo
Abstract : Objective: To compare the effects of respiratory function on different degrees of reduced thoracic volume and evaluate the tolerance of rats with reduced thoracic volume, and to assess the feasibility of thoracic volume as a measure of the severity of rib fractures. Methods: A total of 24 10‐week‐old female Sprague–Dawley (SD) rats were randomly divided into four groups (n = 6 in each group) according to the displacement degree of bilateral rib fractures (2, 4, 6, and 8 mm). The respiratory function of the rats（Tidal volume, Inspiration time, Expiration time, Breath rate, Minute volume, Peak inspiration flow) measured via whole‐body barometric plethysmography before and after operation for 14 consecutive days. Respiratory function parameters of each group were analyzed. Chest CT scans were performed before and 14 days after operation, after that we reconstructed three‐dimensional of the thoracic and lung and measured their volumes by computer software. We calculated the percentage of thoracic and lung volume reduction after operation. Results: At the 14th day after the operation, the decline of thoracic volume rates of in the 2, 4, 6, and 8 mm groups were 5.20%, 9.01%, 16.67%, and 20.74%, respectively. The 8 mm group showed a significant reduction in lung volume. The postoperative tidal volumes were lower in each of the groups than the baseline values before the operation. The tidal volume of the 2 mm group gradually recovered after the operation and returned to a normal level (1.54 ± 0.07 mL) at 14th day after the operation. The tidal volume of the 4, 6, and 8 mm groups recovered gradually after the operation, but did not return to baseline level at the 14th day. In particular, the tidal volume of the 8 mm group was significantly lower than that of the other groups during the 14 days (1.23 ± 0.12 mL, p  < 0.05). There were no significant changes in the inspiratory and expiratory times, peak inspiratory and expiratory flows, respiratory rate, and minute ventilation during the 14 days after the operation in each group. Conclusions: Displaced rib fractures lead to thoracic collapse and reduced thoracic volume, which can affect tidal volume in rats. The greater the decrease of thoracic volume, the more obvious the decrease of early tidal volume. The thoracic volume can be used as an objective parameter to evaluate the severity of multiple rib fractures. Early operation to restore thoracic volume may improve early respiratory function. Decreased thoracic volume affected respiratory function and can be compensated and recovered in the long term. Abstract : In this study, we made four groups of animal models of multiple rib fractures in rats to compare the effects of different degrees of reduced thoracic volume on respiratory function tolerance.